Thermal induction and overexpression of a foreign protein in 'Escherichia Coli' culture - Razali, Firdausi (2002)
Engineering studies were performed on foreign protein production by a recombinant Escherichia coli, which overexpresses intracellular Ecoli P-galactosidase from the plasmid vector pBRG 401 under transcriptional regulation of the ?pL promoter and cL857 protein repressor. Both genetic/physiological and environmental/bioprocess factors that influenced the performance and the kinetics of protein expression and growth in complex medium were investigated. A novel approach in describing protein expression in the thermal induction system in an E.coli culture was proposed. The disappearance of protein expression during induction was primarily due to plasmid instability. The instability was non-segregational, irreversible, and strongly temperature-dependent. The loss of resistance towards the selective pressure was in parallel with the decline of protein expression, despite the fact that both events were regulated by separate promoters. The absence of inclusion bodies implied that the overexpressed proteins were completely soluble. The occurrence of intraceliular proteolysis was not evident during the induction. However, proteolysis was observed even in the presence of a respiratory inhibitor at extended incubation time if glucose was present. This proved that the additional metabolic energy needed for the protein degradation was minimal. Although oxygen concentration was not a limiting factor in the culture, the increased secretion of acetic acid following protein overexpression signified a shift of metabolism from oxidative to fermentative pathway. This resulted in a feedback repression in the Kreb's cycle, with consequently lowering the metabolic overload due to reduced protein expression on the plasmid. The accumulated acetic acid and the acidic pH lowered both growth and protein expression. However, in the absence of acetic acid, the growth seemed unaffected by pH. The exclusion of glucose during the induction phase in complex medium was beneficial. The average specific enzyme activity decreased from 95.3 U/mg in the absence of glucose to 20.5 U/mg when glucose was present at an induction temperature of 42 OC. Complex-substrate concentrations also affected plasmid stability, and hence determined protein expression levels. One may conclude that the inactivation of plasmid was not due to temperature per se, but rather due to the negative effect of a strong promoter and protein expression on the plasmid. The average specific productivity decreased as the induction time elapsed. The plateau in productivity marked the complete inactivation of plasmid, and hence the end of protein expression. The decline of the total viable cell counts during the induction was mainly due to the metabolic load. When the culture was totally freed from the productive population, the total viable cell count started to incline. The increase of biomass from the unproductive cells resulted in the decline of the total specific protein activity in the culture. The time of the incline coincided with the time where all the resistant (productive) cells completely disappeared from the culture. A novel semi-empirical model was developed to describe the kinetics of protein expression, growth, and plasmid stability. Good agreement between the predicted and experimental results, in both instantaneous and ramped induction studies, demonstrated the applicability of the model. A novel approach to predicting the induction temperature operating range was established and experimentally proven between 37.3 OC and 42 OC in this study. The ultimate specific P-galactosidase activity ranged from 66 U/mg to 149 U/mg at induction temperature of 42 OC and 38 OC respectively. This approach also provided an accurate means of estimating the average plasmid number per cell at a given time and temperature during the induction. The dependence of parameters on the temperature was determined using an Arrhenius relationship. The temperature strongly affected the plasmid decay constant (h) and the number of activated plasmids per cell (n), while the specific growth rate (U) was relatively independent. This suggested that the protein expression and growth were uncoupled. In addition, the maximum biomass concentration (Xmax), the proteolysis rate (Kprot), and lysis rate (Klys) were also barely influenced by temperature.